Tata Cara Pelayanan dan Penerbitan Akta Kelahiran pada Dinas Kependudukan dan Catatan Sipil Kabupaten Aceh Timur - Ruaina; M Djamil HS (Yayasan Kawanad, 2023)
.This research aims to investigate the procedures for servicing and issuing birth certificates at the Population and Civil Registry Service of East Aceh Regency. Descriptive research methods are used to describe and analyze the population administration process. The research population involved Department officials and the community who administer birth certificates, with samples selected purposively. Interviews and document analysis were used as data collection techniques. The research results show that there are two ways to process a birth certificate, namely directly at the Department office and through online services. Technical, administrative, and social barriers were identified, including limited technological infrastructure, high printing costs, and public misunderstanding. Recommendations include improving technological infrastructure, revising tariff policies, and more intensive outreach campaigns